PENGERTIAN, RUANG LINGKUP, TUJUAN, DAN MANFAAT MEMPELAJARI INOVASI BAHAN AJAR PAI - Sirajuddin (Journal of Contemporary Indonesian Islam, 2025)
Islamic Religious Education (IRE) is an important component of the national education system that serves to instill moral values, ethics, and faith in students. However, in practice, IRE instruction often still relies on conventional methods that are unengaging and ill-suited to the characteristics of today's digital generation. This results in low student interest and suboptimal understanding of Islamic values. Therefore, innovation in PAI teaching materials has become an urgent necessity to achieve more effective and contextual learning. Innovation in teaching materials not only involves the development of printed materials but also the creation of strategies, media, and learning approaches that are relevant to technological advancements and the needs of students. This paper discusses the definition, scope, objectives, and benefits of studying PAI teaching material innovation. The scope covers materials on creed, the Qur'an and Hadith, ethics, jurisprudence, and Islamic cultural history. Meanwhile, the objectives and benefits of teaching material innovation include improving learning effectiveness, providing materials that meet student needs, and strengthening teacher competencies. With innovative teaching materials, the learning process can be more communicative, engaging, and meaningful. In conclusion, innovation in PAI teaching materials is a strategic step toward creating relevant, inspiring religious education that can address the challenges of the times. Keywords: Innovation, Teaching Materials, Islamic Religious Education, PAI, Learning, Learning Media